Shiga Toxin 1, as DNA Repair Inhibitor, Synergistically Potentiates the Activity of the Anticancer Drug, Mafosfamide, on Raji Cells - Piero Sestili; Pier Giorgio Petronini; Roberta R. Alfieri; Pier Luigi Tazzari; Francesca Ricci; Pasqualepaolo Pagliaro; Laura Rocchi; Cinzia Calcabrini; Maurizio Brigotti; Valentina Arfilli; Domenica Carnicelli (Toxins, 2013)
Shiga toxin 1 (Stx1), produced by pathogenic Escherichia coli, targets a restricted subset of human cells, which possess the receptor globotriaosylceramide (Gb3Cer/CD77), causing hemolytic uremic syndrome. In spite of the high toxicity, Stx1 has been proposed in the treatment of Gb3Cer/CD77-expressing lymphoma. Here, we demonstrate in a Burkitt lymphoma cell model expressing this receptor, namely Raji cells, that Stx1, at quasi-non-toxic concentrations (0.05–0.1 pM), inhibits the repair of mafosfamide-induced DNA alkylating lesions, synergistically potentiating the cytotoxic activity of the anticancer drug. Conversely, human promyelocytic leukemia cells HL-60, which do not express Gb3Cer/CD77, were spared by the toxin as previously demonstrated for CD34+ human progenitor cells, and hence, in this cancer model, no additive nor synergistic effects were observed with the combined Stx1/mafosfamide treatment. Our findings suggest that Stx1 could be used to improve the mafosfamide-mediated purging of Gb3Cer/CD77+ tumor cells before autologous bone marrow transplantation.